The perception of UiTM Sarawak student on the quality policy practices case study : Mara University of Technology/ Glenn Lores … [et.al.] - Lores, Glenn; Ajin, Taddy; Nyelang, Debbie Jenggut; Unjil, Yak Philomena; Lanyau, Margaret (2023)
This study is study to investigate, analyze and identify the various perceptions of the quality policy in UITM and the effectiveness of the quality practices. Here, a study is conducted to research on the services provided by the Security Unit, Health Unit and Environment Unit and their management to the students, UITM’s goods and facilities and also to the regards of the types of quality practices that are implemented in UITM. Thus, in this study various type of methods are use to collect the accurate data and information that are require by the researchers of this study. These methods include distribution of questionnaire methods, interview methods, observation method, and also the use of retrieving information via internet. Then, these data will be analyzed by using the SPSS system. In addition in this study, 100 students had been selected as the sample of this study. These students are the respondents for the study and they are requiring answering the questionnaires. The success of this study is base on their responses.